Ethnic issues and the functioning of Silesia as a region in the years 1918-1945 - Strauchold, Grzegorz (Publishing House eBooki.com.pl, 2014)
The 20th century was among the most dramatic in the history of Silesia. At the turn of the 20th century, Prussia and the German Reich as a whole saw the emergence of a modern German nation. As a result, the German nation, dominant in Silesia, was to become a paragon for all ethnically non-German populations. Social changes resulting from World War I cemented the formation of the German nation and also hastened the formation of Polish national sentiment in Upper Silesia. At the same time, a group of Upper Silesians not possessed of the idea of belonging to a nation while feeling strongly connected to their region was always in existence, and this group does not lend itself readily to easy analysis. Attention must also be paid to the activities of Silesian nationals (the so called Schlonsaken). The partition of Silesia (primarily Upper Silesia) between Germany and a reconstituted Poland had a chaotic influence on the worldview of many of the inhabitants of this land. Many Germans found themselves within the borders of the new Polish state, which they did not accept, while many Upper Silesians felt dissatisfied and unappreciated within the Polish Republic. During World War II, Upper Silesia, which previously captured both German and Polish identities, was subjected to an intensive policy of Germanization following its unlawful incorporation into the Reich in 1939. This policy also attracted many to the ideas of National Socialism. These factors were undoubtedly both cohesive and disruptive to the inhabitants of this land.
Keywords: Polonisation; Germanisation; Czechisation; Silesianess